A STUDY OF JOB SATISFACTION OF WOMEN LECTURER WORKING IN INTERMEDIATE COLLEGES IN AHMEDNAGR DISTRICT - Gurung, Shabnam (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper study the job satisfaction of women lecturer working in intermediate colleges in Ahmednagar District. This present study studied the various factors that affect the job satisfaction of women lecturer working in intermediate colleges. This study undertakes the factors like work, salary, working condition, promotion and job security for studying the job satisfaction level of the respondents. All these factors are important determinants for job satisfaction. Finding states that all employees are satisfied with the job and they have positive level of job satisfaction. These satisfied employees are highly committed towards their work and the organization and happy in their personal life.